Conversion of isotropic fluorescence into a long-range non-diverging beam. (25th January 2018) - Zhang, Douguo; Zhu, Liangfu; Chen, Junxue; Wang, Ruxue; Wang, Pei; Ming, Hai; Badugu, Ramachandram; Rosenfeld, Mary; Zhan, Qiwen; Kuang, Cuifang; Liu, Xu; Lakowicz, Joseph R
Abstract: Fluorescent samples typically emit isotropically in all directions. Large lenses and other optical components are needed to capture a significant fraction of the emission, and complex confocal microscopes are required for high resolution focal-plane imaging. It is known that Bessel beams have remarkable properties of being able to travel over long distances, over 1000 times the wavelength, without diverging, and hence are called non-diffracting beams. In previous reports the Bessel beams were formed by an incident light source, typically with plane-wave illumination on a circular aperture. It was not known if Bessel beams could form from fluorescent light sources. We demonstrate transformation of the emission from fluorescent polystyrene spheres (FPS) into non-diverging beams which propagate up to 130 mm (13 cm) along the optical axis with a constant diameter. This is accomplished using a planar metal film, with no nanoscale features in the X – Y plane, using surface plasmon-coupled emission. Using samples which contain many FPS in the field-of-view, we demonstrate that an independent Bessel beam can be generated from any location on the metal film. The extremely long non-diffracted propagation distances, and self-healing properties of Bessel beams, offer new opportunities in fluorescence sensing and imaging.